Leadership styles in Ecuadorian companies: application of the Multifactor Leadership Questionnaire (MLQ) - Melean Romero, Rosana Alejandra; Manosalvas Vaca, Carlos Aníbal; Guerrero Bejarano, María Auxiliadora; Hermenegildo, Arturo Mercado; De la Torre Tejada, José Abel (Business: Theory and Practice, 2023)
Leadership has been widely studied worldwide, emphasizing changes that individuals with particular qualities achieve from the transformational and transactional. The objective is to evaluate the relationship between transformational and transactional leadership styles taking into account the effort and effectiveness perceived by followers in Ecuadorian public and private companies. Visions of seminal authors are analyzed on the subject Avolio and Bass, Emeka, Feliciano et al., Gutiérrez et al., Mirzani, among others. The research was quantitative, non-experimental, cross-sectional, and explanatory. The MLQ instrument (Avolio & Bass, 1991) was used, the sample was non-probabilistic for convenience, with 519 workers from Ecuador participating. SPSS V25 and SmartPLS4 software were used. Don’t exist significant differences in transformational leadership about gender, but there are in transactional leadership. By type of company, it was evidenced that there are no significant differences regarding transformational leadership, more so when analyzing transactional leadership. Men apply transactional leadership to a greater extent than women, demonstrating that transformational leadership is applied in the private sector in a higher percentage. Gender moderates the relationship between transformational leadership and effort, as well as the relationship between transactional leadership with effort and effectiveness. No evidence of any moderating effect of company type on the relationship between leadership styles and effort was found.